The microplastisphere: Biodegradable microplastics addition alters soil microbial community structure and function. (May 2021) - Zhou, Jie; Gui, Heng; Banfield, Callum C.; Wen, Yuan; Zang, Huadong; Dippold, Michaela A.; Charlton, Adam; Jones, Davey L.
Abstract: Plastics accumulating in the environment, especially microplastics (defined as particles <5 mm), can lead to a range of problems and potential loss of ecosystem services. Polyhydroxyalkanoates (PHAs) are biodegradable plastics used in mulch films, and in packaging material to minimize plastic waste and to reduce soil pollution. Little is known, however, about the effect of microbioplastics on soil-plant interactions, especially soil microbial community structure and functioning in agroecosystems. For the first time, we combined zymography (to localize enzyme activity hotspots) with substrate-induced growth respiration to investigate the effect of PHAs addition on soil microbial community structure, growth, and exoenzyme kinetics in the microplastisphere (i.e. interface between soil and microplastic particles) compared to the rhizosphere and bulk soil. We used a common PHAs biopolymer, poly (3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) and showed that PHBV was readily used by the microbial community as a source of carbon (C) resulting in an increased specific microbial growth rate and a more active microbial biomass in the microplastisphere in comparison to the bulk soil. Higher β-glucosidase and leucine aminopeptidase activities (0.6–5.0 times higher V max ) and lower enzyme affinities (1.5–2.0 times higher K m ) were also detected in the microplastisphere relative to the rhizosphere. Furthermore, the PHBV addition changed the soil bacterial community at different taxonomical levels and increased the alpha diversity, as well as the relative abundance of Acidobacteria and Verrucomicrobia phyla, compared to the untreated soils. Overall, PHBV addition created soil hotspots where C and nutrient turnover is greatly enhanced, mainly driven by the accelerated microbial biomass and activity. In conclusion, microbioplastics have the potential to alter soil ecological functioning and biogeochemical cycling (e.g., SOM decomposition). Graphical abstract: Image 1 Highlights: Microplastisphere (soil-MPs interface) is localized and visualized by zymography. MPs stimulates microbial turnover and nutrient efficiency in microplastisphere. MPs increases soil enzyme activity and shifts bacterial community to K -strategy. MPs have the potential to alter soil functioning and biogeochemical cycling.